Literary territories : cartographical thinking in late antiquity - Johnson, Scott Fitzgerald (Oxford University Press, 2016)
'Literary Territories' argues that the literature of Late Antiquity shared a defining aesthetic sensibility which treated the classical 'inhabited world', the oikoumene, as a literary metaphor for the collection and organization of knowledge